2018
DOI: 10.1038/s41598-018-30491-w
|View full text |Cite
|
Sign up to set email alerts
|

Stress affects the epigenetic marks added by natural transposable element insertions in Drosophila melanogaster

Abstract: Transposable elements are emerging as an important source of cis-acting regulatory sequences and epigenetic marks that could influence gene expression. However, few studies have dissected the role of specific transposable element insertions on epigenetic gene regulation. Bari-Jheh is a natural transposon that mediates resistance to oxidative stress by adding cis-regulatory sequences that affect expression of nearby genes. In this work, we integrated publicly available ChIP-seq and piRNA data with chromatin imm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2
2

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…Percentages of divergence to consensus were evaluated from RepeatMasker output .align file using A. Kapusta script [154] upregulation of Jheh1 and Jheh2 [166]. Second, the spread of repressive epigenetic marks targeting TEs can reduce the expression of nearby genes (see below, host defenses against TEs), as it was also demonstrated in the Jheh cluster [167]. Lee and Karpen demonstrated recently that the spread of repressive epigenetic marks to nearby DNA occurs for more than half of euchromatic TEs, and can extend up to 20 kb [12].…”
Section: Impacts Of Tesmentioning
confidence: 99%
“…Percentages of divergence to consensus were evaluated from RepeatMasker output .align file using A. Kapusta script [154] upregulation of Jheh1 and Jheh2 [166]. Second, the spread of repressive epigenetic marks targeting TEs can reduce the expression of nearby genes (see below, host defenses against TEs), as it was also demonstrated in the Jheh cluster [167]. Lee and Karpen demonstrated recently that the spread of repressive epigenetic marks to nearby DNA occurs for more than half of euchromatic TEs, and can extend up to 20 kb [12].…”
Section: Impacts Of Tesmentioning
confidence: 99%
“…For example, TEs have been shown to add transcription factor binding sites, and transcription start sites, leading to changes in expression of nearby genes (33)(34)(35)(36). TEs can also influence gene expression by inducing changes in the chromatin structure (37)(38)(39). These changes in expression induced by TE insertions have been associated with several organismal phenotypes such as stress resistance and fertility (40)(41)(42).…”
Section: Introductionmentioning
confidence: 99%
“…When they examined the neighbouring genes to these insertions, they found they were genes previously known to be involved in adaptation to a variety of environmental factors (González et al, ). Other studies have also found direct links between the presence of the insertion and adaptive phenotypes related to insecticide resistance (Magwire, Bayer, Webster, Cao, & Jiggins, ; Merenciano, Ullastres, Cara, Barrón, & González, ), cold stress response, oxidative stress (Guio, Barrón, & González, ; Guio, Vieira, & González, ), xenobiotic stress (Mateo, Ullastres, & González, ) and resistance to sigma virus (Magwire et al, ). Thus, there is growing evidence that TEs can be under selection to alter patterns of expression on neighbouring genes, leading to adaptive changes in phenotypes.…”
Section: Transposable Elements In Invasive Populationsmentioning
confidence: 92%